Existence of a smooth solution of one boundary-value problem - Khoma, N. H. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study a periodic boundary-value problem for the quasilinear equationu tt−uxx=F[u, ut], u(0, t)=u(π, t)=0,u(x, t+2π)=u(x, t). We establish conditions that guarantee the validity of the uniqueness theorem.